RENDEMEN EKSTRAK ETANOL HERBA RUMPUT AKAR WANGI (Polygala paniculata L) PADA PERBANDINGAN KONSENTRASI PELARUT - Pradana, Anugerah Riska; Wahyudi, Hendra; Lestari, Dwi (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2023)
Rumput akar wangi (Polygala paniculata (L)) belongs to the Polygalaceae family. One of the extract yields is influenced by solvent concentration. The aim of the research is to determine the effect of variations in concentration on the yield of Polygala paniculata extract and the groups of compounds in the extract. This research includes determination, collection, and plant preparation, processing of Polygala paniculata simplicia, extraction, screening, and determination of yield. In this study, 50 grams of Polygala paniculata powder were extracted with different solvent concentrations, namely 70% and 95% ethanol using the maceration method. Replication was carried out on each solvent three times. Data were analyzed using descriptive methods and processed using SPSS (Statistical Product and Service Solutions) tools. The results of phytochemical screening showed that the extract contained flavonoids, tannins, saponins, and terpenoids. The calculation results of the ethanol extract of Polygala paniculata were 70% ethanol (17.77% ± 1.34) and 95% ethanol (12.59% ± 0.86). The SPSS test results on the Independent Samples Test show that there is a significant difference (p < 0.05). The highest yield of Polygala paniculata extract was obtained using 70% ethanol for filtration.